Atypical cortical thickness and folding of language regions in Chinese nonsyndromic cleft lip and palate children after speech rehabilitation - Wang, Shi; Fang, Lei; Miao, Guofu; Li, Zhichao; Rao, Bo; Cheng, Hua (Frontiers in Neurology, 2022)
Objective Even after palatoplasty and speech rehabilitation, patients with cleft lip and palate (CLP) remain to produce pronunciation errors. We hypothesized that nonsyndromic CLP (NSCLP) after speech rehabilitation had structural abnormalities in language-related brain regions. This study investigates structural patterns in NSCLP children after speech rehabilitation using surface-based morphometry (SBM) analysis. Methods Forty-two children with NSCLP and 42 age- and gender-matched healthy controls were scanned for 3D T1-weighted images on a 3T MRI scanner. After reconstructing each brain surface, we computed SBM parameters and assessed between-group differences using two-sample t-tests and permutation tests (5,000 times). Then, we assessed the relationship between the SBM parameters and the Chinese language clear degree scale (CLCDS) using Pearson's correlation analysis. Result The speech-rehabilitated children with NSCLP showed lower cortical thickness and higher gyrification index mainly involving left language-related brain regions (permutation tests, p < 0.05). Furthermore, the lower cortical thickness of the left parahippocampal gyrus was positively correlated with CLCDS scores (r = 0.370, p = 0.017) in patients with NSCLP. Conclusion The SBM analysis showed that the structural abnormalities of speech-rehabilitated children with NSCLP mainly involved language-related brain regions, especially the dominant cerebral hemisphere. The structural abnormalities of the cortical thickness and folding in the language-related brain regions might be the neural mechanisms of speech errors in NSCLP children after speech rehabilitation. The cortical thickness of the parahippocampal gyrus may be a biomarker to evaluate pronunciation function.